Desafios e oportunidades dos projetos de energia renovável registrados no primeiro período do protocolo de Quioto - Falleiro, Alice de Moraes (2015)
10 years ago it entered into force global climate agreement Kyoto Protocol, as an attempt to curb emissions of greenhouse gases (GHG) with the help of three flexibility mechanisms, including the Clean Development Mechanism (CDM). The clash between developing countries, which have proven resistant to the idea of having mandatory reduction targets in the post-Kyoto period and developed countries, which support the idea of developing countries spend to have binding targets to reduce GHG emissions is presented as the great debate that hangs in the negotiations that lead to continuity of a post 2020 global climate agreement this sense Brazil committed through voluntary GHG reduction targets through the National Climate Change Policy. Therefore, this work aims to identify the challenges and opportunities of renewable energy projects located in Brazil, recorded in the first period of the Kyoto Protocol and that have been developed according to ACM0002 methodology from the perspective of the companies owning the projects and consultancies who develop them. Secondary data available were used on the websites of United Nations Framework Convention on Climate Change (UNFCCC) and the Ministry of Science, Technology and Innovation (MCTI). Primary data were obtained from a questionnaire with the target audience. Still, Fisher's exact statistical tests, and Wilcoxan were performed. From this, it was concluded that consultancies and companies showed significant similarity with regard to the challenges and opportunities faced by projects. This is due to the fact that the problems associated with CDM projects are significant since the structuring of project eligibility to be submitted to the UNFCCC to the carbon market, which has excess supply and low demand front. Still, it was found that the issues directly to the CDM, in turn, showed greater difference between the answers of respondents with respect to the carbon credit market. This can be linked to the fact that a stable carbon market increases the chance for companies to negotiate their claims in the market and achieve drain, at a price that guarantees return on investment and fosters the consultants develop new projects in this market